Companionship in code: AI’s role in the future of human connection - Marta Andersson (Humanities & Social Sciences Communications)
As research shows, AI chatbots have increasingly taken on the role of human companions, offering what can be dubbed ‘emotional fast food’: a convenient substitute for connection—instantly gratifying, but ultimately lacking substance. This comment explores how AI mimics emotional understanding and closeness, and how such simulations shape user perceptions of its role. By considering both potential risks and benefits, the article reflects on the growing trend of using AI for companionship and its troubling social ramifications. Far from innocuous, this development raises existential and philosophical questions, inviting consideration of what it reveals about our evolving relationships with technology and with each other.